Penerapan Corporate Social Responsibility (CSR) terhadap Kinerja Keuangan Perusahaan dan Pencapaian SDGs di Indonesia - Anas Tasya Angely Fidausya; Ajeng Tita Nawangsari (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2026)
This study examines the application of Corporate Social Responsibility (CSR) to corporate reputation and the achievement of Sustainable Development Goals (SDGs) in Indonesia. The background of the study shows that CSR has become an important aspect in the operations of modern companies, especially after being mandated by Law No. 40 of 2007, with a strategic role in supporting the achievement of the 2030 SDGs. This study uses the framework of stakeholder theory and legitimacy theory to analyze the relationship between CSR, corporate reputation, and its contribution to the SDGs. The research method used is a literature review with a descriptive qualitative approach. Data collection was carried out through a literature study of laws and regulations, scientific journals, and scientific articles for the period 2020-2024. The research findings show that the implementation of CSR in Indonesia is driven by clear regulations and requires intensive collaboration between companies, the government, and the community. CSR has been proven to have a significant impact on corporate reputation by increasing consumer trust and loyalty. Effective CSR implementation contributes positively to the achievement of the SDGs with a strategic approach that integrates community involvement, environmental sustainability, and technological innovation. This study concludes that CSR plays a vital role in building a company's reputation and supporting sustainable development in Indonesia.